Ramadan Observance Exacerbated the Negative Effects of COVID-19 Lockdown on Sleep and Training Behaviors: A International Survey on 1,681 Muslim Athletes - Romdhani, Mohamed; Ammar, Achraf; Trabelsi, Khaled; Chtourou, Hamdi; Vitale, Jacopo A.; Masmoudi, Liwa; Nédélec, Mathieu; Rae, Dale E.; Al Horani, Ramzi A.; Ben Saad, Helmi; Bragazzi, Nicola; Dönmez, Gürhan; et al. (Frontiers in Nutrition, 2022)
Objective: Disrupted sleep and training behaviors in athletes have been reported during the COVID-19 pandemic. We aimed at investigating the combined effects of Ramadan observance and COVID-19 related lockdown in Muslim athletes. Methods: From an international sample of athletes (n = 3911), 1681 Muslim athletes (from 44 countries; 25.1 ± 8.7 years, 38% females, 41% elite, 51% team sport athletes) answered a retrospective, cross-sectional questionnaire relating to their behavioral habits pre- and during- COVID-19 lockdown, including: (i) Pittsburgh sleep quality index (PSQI); (ii) insomnia severity index (ISI); (iii) bespoke questions about training, napping, and eating behaviors, and (iv) questions related to training and sleep behaviors during-lockdown and Ramadan compared to lockdown outside of Ramadan. The survey was disseminated predominately through social media, opening July 8th and closing September 30th, 2020. Results: The lockdown reduced sleep quality and increased insomnia severity (both p<0.001). Compared to non-Muslim (n=2230), Muslim athletes reported higher PSQI and ISI scores during-lockdown (both p<0.001), but not pre-lockdown (p>0.05). Muslim athletes reported longer (p<0.001; d=0.29) and later (p<0.001; d=0.14) daytime naps, and an increase in late-night meals (p<0.001; d=0.49) during- compared to pre-lockdown. Both sleep quality (χ2=222.6; p<0.001) and training volume (χ2=342.4; p<0.001) were lower during-lockdown and Ramadan compared to lockdown outside of Ramadan in the Muslims athletes. Conclusion: Muslim athletes reported lower sleep quality and higher insomnia severity during- compared to pre-lockdown, and this was exacerbated by Ramadan observance. Therefore, further attention to Muslim athletes is warranted when a circadian disrupter (e.g., lockdown) occurs during Ramadan.